Motives, choice of entry mode, and challenges of bank internationalization: Evidence from China. (31st March 2019) - He, Weijing; Boateng, Agyenim; Ring, Patrick
Abstract : This study examines the motives, entry mode choice, and challenges of the international expansion in an emerging country context. Data were collected via interviews from 30 senior managers based on a sample of 10 Chinese commercial banks (CCBs) involved in international expansion over the period of 2001–2013. This study finds greenfield and mergers and acquisitions are the most popular foreign entry mode used by CCBs. The motives of emerging market banks' internationalization appear to be intrinsically linked to market development to serve customers operating in overseas market, government policies, and strategic knowledge sourcing. In terms of challenges, the study finds lack of management resources/technical capacity, culture, adapting to the host country regulatory environment, and lack of experience to be the main challenges to bank internationalization.